Russian Institute of Roman Law in Berlin in Light of I. A. Pokrovskij’s Scholarly Training - Vasilyev, Andrey (Hyperboreus, 2016)
The paper surveys a history of the Russian Institute of Roman Law in Berlin and of its inﬂuence on I. A. Pokrovskij, who were trained there and afterwards became one of the most famous Roman law scholars in Russia. The origins of this educational institution are traced and the opposition to it of Russian professorial body (N. P. Bogolepov, B. V. Nikolskij) examined. The author comes to the conclusion that the Institute advanced the scholarly contacts between Russia and Germany but was doomed to be short-lived, because it failed to meet the government political expectation.